An exploratory study of the SCM practices and IT usage: an emerging market context. (1st October 2010) - Singh, Amar; Narain, Rakesh; Yadav, Ramesh Chandra
Supply chain management has become a critical source of sustainable advantage. Connectivity with all the partners and ability to communicate rapidly and accurately along the supply chain with customers and suppliers, using information technology tools, is essential. This paper reports the findings of a postal survey carried out in 54 Indian manufacturing organisations to ascertain the impact of information technology on supply chain management practices. The findings indicate that the use of electronic means of communication, such as e-markets, electronic data interchange and extranets will increase along with e-mails. The use of supply chain planning and control tools and techniques such as APS, VMI, CPFR etc. are in their infancy stage. The organisations intend to invest heavily in information technology to encourage adoption of e-business. Large organisations are ahead of the small and medium enterprises in the usage of information technology in different functional areas.